Ultrasound elastography of muscles in cerebral palsy: systematic review - V. M. Kenis; A. V. Sapogovskiy; E. V. Melchenko; O. E. Agranovich; A. I. Shubina; M. V. Zhurbitskaya (Нервно-мышечные болезни, 2022)
Quantitative analysis of skeletal muscles in cerebral palsy is an important but unsolved problem. Ultrasound elastography is a group of diagnostic methods that allow visualizing tissue stiffness, measuring and displaying biomechanical properties of tissues. The aim of our study was to conduct a systematic analysis of literature on ultrasound elastography of skeletal muscles in children with cerebral palsy.A literary search for keywords in the databases PubMed, Google Scholar, eLIBRARY was carried out. The inclusion criteria were nosology (cerebral palsy), age (up to 18 years) and the study design (original study in ultrasound elastography of the skeletal muscler), as well as the availability of detailed information about the technical issues, demographic and clinical data.The final analysis included 20 publications. Patients with hemiplegic cerebral palsy were most often studied, with the healthy side used as a control, shear wave elastography was used more often, in which both share wave velocity and shear modulus were assessed, and linear probes were used more often. The most frequent anatomical objects were the calf muscles. Most often, elastography was used to assess the results of botulinum therapy, and demonstrated an increase in muscle elasticity after treatment.Ultrasound elastography as a method od assessment of the mechanical properties of skeletal muscles in children with cerebral palsy cannot be considered suitable as a routine study at the moment. But the method showed promising results for the research purposes: all the publications we analyzed demonstrated significant difference in elastography indicators both when comparing with unaffected limb or with healthy controls. Positive changes were also detected after various therapeutic interventions aimed to reducing muscle tone and retraction e. g. botulinum toxin injections.The absence of a unified approach to muscle elastography in children with cerebral palsy was demonstrated, both for data obtaining and interpretation. In general, ultrasound elastography of the skeletal muscles in children with cerebral palsy is a promising method for qualitative and quantitative assessment of muscle tissue that requires further development. Improvement of technology, standardization of technique and measurements will further expand the usage of this method.